A Life Lived in Class - Diane Reay (PRISM)
I have spent my whole life in ‘class’, first as a working-class girl and then as a primary school teacher, and later as an academic. My academic career spans over twenty-five years taking the work of Pierre Bourdieu to the limit. Taking Bourdieu’s work to the limits is to engage with his research affectively as well as intellectually, to recognise our own social and academic positioning in the same powerful way he recognised and worked with his own autobiography (Bourdieu, 2007). It also requires the deconstruction and reconstruction of his concepts in relation to our own distinct experiences. In this article I attempt to tease out the many different and antagonistic embodiments of the relationship between a habitus and a field, taking myself as a case study. I am going to focus on two fields: the working-class coal-mining community of my childhood and youth, and the educational system.